A mindfulness-based intervention improves perceived stress and mindfulness in university nursing students: a quasi-experimental study - Liu, Yi-Ling; Lee, Chao-Hsien; Wu, Li-Min (Scientific reports, 2024)
University nursing students have been shown to experience psychological stress. A mindfulness-based intervention (MBI) may be a helpful tool for stress management. The aim of this study was to examine the effects of a MBI on improving mindfulness and reducing perceived stress in nursing students. A quasi-experimental study was conducted between July 2021 and February 2022. The intervention group participated in an 8-week mindfulness awareness course, which included 50 min of training and practice in mindfulness meditation techniques each week. Over the same 8 weeks, the control group watched a 50-min film each week. The mindful attention awareness scale (MAAS) and perceived stress scale (PSS) were administered before the intervention, intervention completion, and 2 and 6 months after the intervention. Data were analyzed using t test and generalized estimating equation. Overall, that the MBI showed a substantial effect on felt stress in comparison to the control group. When compared to the control group, the MBI showed a substantial impact on trait mindfulness. The MBI was beneficial for nursing students and could be considered a viable approach in nursing education to enhance mental wellbeing. It could be an effective method of relieving stress in a high-stress population.